(untitled) (Papeles, 2017)
La BBC en 1986 le realizó una breve entrevista al entonces estudiante de Cambridge David Dewey (estudiante primero y luego colega de Dario Fo) quien profirió el siguiente comentario respecto del teatro: “There’s no point today in talking about poetry and theatre as living literature genres. With the rise and down of postmodernism those two genres can’t mean, or do, what they used to”. Es precisamente con esta acotación que la profesora Dietrich Holland introduce al lector en su más reciente libro: What is Called Theatre Nowadays?